Clinical and radiographic outcomes of hip resurfacing arthroplasty after eight years – a retrospective study() - Bessa, Felipe Spinelli (Rev Bras Ortop, 2018)
OBJECTIVE: To assess the clinical and radiographic outcomes of hip resurfacing arthroplasty for the treatment of hip osteoarthritis. METHODS: This study retrospectively assessed 30 patients with hip osteoarthritis who underwent hip resurfacing arthroplasty between 2005 and 2014. Patients of both genders suffering from advanced primary and secondary hip osteoarthritis were included in the study. Data were collected about postoperative complications and the need for revision of the arthroplasty. Antero-posterior pelvis and lateral hip x-rays were performed in order to classify osteolysis according to the Amstutz criteria; the Lequèsne index of severity for osteoarthritis of the hip and the UCLA activity level questionnaires were answered pre- and postoperatively. RESULTS: After a mean follow-up of eight years, a statistically significant improvement was observed between the mean of the outcomes of both scores, when compared pre- and postoperatively (p < 0.001). Nevertheless, there was a high incidence of arthroplasty revision (20%), related to the size of the femoral stem and errors in surgical technique. CONCLUSION: Using the appropriate technique, hip resurfacing arthroplasty can present good results in well-selected patients.